Perspectives of Bank International Development: Case of Wells Fargo & Co - Hang Shu; Elena V. Kolganova (Communications of International Proceedings, 2021)
Each firm has its own interesting experience and strategy for entering the business space, so that it can be implemented there at a low cost of money and effort. And at the same time, they follow it for many years, despite the great competition among their potential business rivals, bypassing them with the quality of the product and the organizational skills of the company's employees. In modern conditions, especially during the crisis and after it, companies need the sustainable support from financial organizations, and this gives the banks the great field for development. Banks’ international development is concerned with serious political constrains and risks. But currently the political situation as becoming warmer even between Russian Federation and USA. Russia is a very perspective market for large banks and that is why the research which results are presented in the article is devoted to the analysis of the possibility of the one of Top-4 USA banks development in RF.
Keywords: transnational bank; internationalization; Wells Fargo & Co; international development